INTERACTION OF LASER RADIATION WITH MATTER. LASER PLASMA : Modification of a graphene–copper substrate in vacuum by femtosecond laser radiation. (28th February 2018) - Mironov, B N; Aseev, S A; Ishchenko, A A; Kochikov, I V; Chekalin, S V; Ryabov, E A
Abstract: The effect of intense femtosecond laser radiation on single-layer graphene fixed on a copper fine-meshed grid is studied using a compact femtosecond electron diffractometer. A modification of the graphene–copper substrate is found. The composition of the resulting compounds is analysed. It is shown that the main new products are copper oxides. The prospects of using such a substrate in the method of ultrafast electron diffraction and microscopy are analysed.